2020
DOI: 10.1155/2020/2981585
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis Improves the Value of Pretreatment 18F-FDG PET/CT in Predicting Interim Response of Primary Gastrointestinal Diffuse Large B-Cell Lymphoma

Abstract: Objectives. To explore the application of pretreatment 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) texture analysis (TA) in predicting the interim response of primary gastrointestinal diffuse large B-cell lymphoma (PGIL-DLBCL). Methods. Pretreatment 18F-FDG PET/CT images of 30 PGIL-DLBCL patients were studied retrospectively. The interim response was evaluated after 3-4 cycles of chemotherapy. The complete response (CR) rates in patients with different clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…We collected 18 papers about radiomics in blood cancers [ 82 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ], most of them focusing on non-Hodgkin lymphoma (11/18) and Hodgkin lymphoma (4/18). The average number of patients included was 77 (median = 51, range, 24–251) and the average number of evaluated textures was 28 (median = 22, range, 3–78), extracted mainly from the GLCM (100%), the GLZSM (56%) and the GLRLM (50%).…”
Section: Resultsmentioning
confidence: 99%
“…We collected 18 papers about radiomics in blood cancers [ 82 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 ], most of them focusing on non-Hodgkin lymphoma (11/18) and Hodgkin lymphoma (4/18). The average number of patients included was 77 (median = 51, range, 24–251) and the average number of evaluated textures was 28 (median = 22, range, 3–78), extracted mainly from the GLCM (100%), the GLZSM (56%) and the GLRLM (50%).…”
Section: Resultsmentioning
confidence: 99%
“…Incidence of extra nodal lymphomas has increased significantly especially in Pakistan [ 7 , 12 ]. Different extra nodal sites are involved out of which, GIT is the most common primary extra nodal site and DLBCL is the most common type of lymphoma in primary gastrointestinal lymphoma [ 13 ]. In our study we enrolled 138 patients with DLBCL and observed the frequency of nodal and primary extra nodal DLBCL in our setup, comprising of patients from all over Pakistan with a large proportion of patients from Northern and tribal areas.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been further refined by calculating the entire metabolic tumor volume (MTV) and the total lesion glycolysis (TLG). Both PET and CT image data can be additionally analyzed by using texture analysis with potential for tumor characterization either in the primary setting (baseline) for prognosis evaluation, or during therapy as an adjunct to morphologic and metabolic changes for more accurate response assessment [ 9 , 10 ]. Finally, some laboratory biomarkers like lactate dehydrogenase (LDH) in serum have been used for a long time as prognostic factors in lymphoma patients.…”
Section: Introductionmentioning
confidence: 99%